Contrasting population genetic structures using allozymes and the inversion polymorphism in Drosophila buzzatii - Rodriguez, C. (2000)
Second chromosome inversion and genotypic frequencies at seven allozyme loci, differentially associated with inversions, were determined in seven natural populations of Drosophila buzzatii. The patterns of variation of allozymes and the inversion polymorphisms were significantly different, indicating the role of adaptive differentiation for the latter. Moreover, the patterns of population structure varied among allozyme loci, suggesting the operation of diversifying selection for certain loci. Differentiation was negligible for Leucyl-amino peptidase (Lap) and Peptidase-2 (Pep-2), low to moderate for Aldehyde oxidase (Aldox), Peptidase-1 (Pep-1) and Esterase-1 (Est-1) and high for Esterase-2 (Est-2) and Xanthine dehydrogenase (Xdh). Significant linkage disequilibria were detected between inversions and Aldox, Est-1, Est-2 and Xdh. Multiple regression analyses of inversion and allele frequencies on environmental variables revealed the existence of clines for inversions, Est-1, Est-2, Xdh and Aldox along altitudinal, latitudinal and/or climatic gradients. Tests using conditional allele frequencies showed that Est-1 and Aldox clines could be accounted for by hitchhiking with inversions, whereas natural selection should be invoked to explain the clines observed for Est-2 and Xdh.